2014
DOI: 10.4103/1658-354x.125898
|View full text |Cite
|
Sign up to set email alerts
|

Use of oral tramadol to prevent perianesthetic shivering in patients undergoing transurethral resection of prostate under subarachnoid blockade

Abstract: Context:Under regional anesthesia, geriatric patients are prone to shivering induced perioperative complications that Anesthesiologists should prevent rather than treat.Aim:We investigated the prophylactic efficacy of oral tramadol 50 mg to prevent the perioperative shivering after transurethral resection of prostate (TURP) surgery under subarachnoid blockade (SAB). Shivering is usually overlooked in patients undergoing urological surgery under spinal anesthesia and may result in morbidity, prolonged hospital … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 19 publications
1
9
0
Order By: Relevance
“…They also act on the thermoregulatory center (temperature control) in the hypothalamus. [ 15 22 ] The results of this study showed that oral TI and Tramadol before surgery decrease intra- and post-operative shivering in patients underwent spinal anesthesia, while there was no significant difference among three groups in terms of some parameters including nausea, vomiting, and hemodynamics. The heart rate of patients in TI group was significantly lower than other groups in recovery.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…They also act on the thermoregulatory center (temperature control) in the hypothalamus. [ 15 22 ] The results of this study showed that oral TI and Tramadol before surgery decrease intra- and post-operative shivering in patients underwent spinal anesthesia, while there was no significant difference among three groups in terms of some parameters including nausea, vomiting, and hemodynamics. The heart rate of patients in TI group was significantly lower than other groups in recovery.…”
Section: Discussionmentioning
confidence: 78%
“…Tewari et al ., in 2014 demonstrated the effect of 50 mg oral tramadol on decreasing shivering during TURP surgery with spinal anesthesia. [ 22 ] Moreover, they compared the effects of oral clonidine and tramadol for preventing shivering in patients underwent TURP with spinal anesthesia and found that both tramadol and clonidine were effective in reducing the severity and duration of shivering. [ 23 ]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tewari et al, 22 study was done to evaluate the efficacy of oral tramadol (50 mg 2 h before surgery) to prevent perioperative shivering in patients undergoing transurethral resection of the prostate under spinal anesthesia. They found a significant reduction in the incidence and severity of perioperative shivering in the study group.…”
Section: Discussionmentioning
confidence: 99%
“…6,8,9 Shivering also may interfere with the monitoring of the patient causing artifacts of electrocardiogram, blood pressure and pulse oxymetry. 7,10 Many therapeutic strategies for treating and prevention of shivering exist. The efficacy of various pharmacological and physical method has already been established.…”
Section: Introductionmentioning
confidence: 99%